Disparities in Anti-Vaccine Views: Twitter Contents Analysis During World Immunization Week - (:unkn) unknown (My University, 2020)
The emergence of social media platforms provides an opportunity to exchange health-related information and express opinions on health-related issues. The researchers' adoption of social media contents in the health research domain is attributed to the easy accessibility of a large number of perspectives and views in limited time and less effort. The analysis of social media contents, such as Twitter, allows researchers to examine people’s perceptions about specific crucial topics, such as vaccinations. The researcher aims to collect and measure data on the current motivations and reasons for opposing vaccination and understand vaccine-skeptics claims against vaccines. This study presents a descriptive quantitative analysis of the contemporary claims against vaccines during the World Immunization Week 2019. The researcher collected 27266 vaccine-related tweets from April 24 – 30, 2019. These tweets were analyzed to characterize key terms and their connections, classified into pre-defined groups, and sentimentally analyzed to identify the anti-vaccine tweets. The tweets analysis captures the anti-vaccine tweets and groups them into themes that were initially created after a manual scanning of a 6,000 tweet sample. The classification and sentiment analyses resulted in 4,181 tweets out of the collected tweets being distributed over eight themes of anti-vaccine views. The results highlight vaccine-skeptics perceptions and motivations not to vaccinate their children. They also view the vaccine's biggest concern among posters which is worrying about vaccine's side effects. The analysis also reveals the anti-vaccine tweets timeline during the World Immunization Week, the top hashtags that were associated with the tweets, and the geo-location posting of these tweets worldwide. The interdisciplinary study of health-related issues in Twitter leads to a better understanding of public concerns and views which will result in greater response to such critical health issues and find solutions to raise health awareness among societies. Advancing the knowledge of methods and patterns of social media contents analyses is becoming an essential tool for the public health domain. Working toward this goal, this study used emerging data analysis approaches to reveal opinions and views against vaccines from Twitter contents to help find solutions to this contemporary critical health issue.